THE EFFECTIVENESS OF USING THE INDONESIAN PRINT MODULE IN IMPROVING STUDENT LEARNING OUTCOME IN SMP ISLAM AL-JAUHARI - Winka Naida; Ardi Mulyana Haryadi; Syifa Lailatul K (Institut Pendidikan Indonesia, 2023)
The low student learning outcomes are influenced by various factors, one of which is the means. One tool that has the potential to improve student learning outcomes is a module. The purpose of the research to be conducted is to determine the effect of the module on student learning outcomes at AlJauhari Islamic Middle School. The method used was a quasi-experimental with a population of class IX students at SMP Islam Al-Jauhari Karangtengah Garut. The samples were selected based on the purposive sampling technique of two classes, namely class IX-A as the control class and class IX-B as the experimental class. The instrument used is a test. Based on the results of the analysis, it is concluded that the use of modules can improve student learning outcomes at Al-Jauhari Islamic Middle School.